Optimized flood control for the Three Gorges Reservoir considering evolving flood propagation trends in the Jingjiang Reach of the Yangtze River - Lan, Lan; Xu, Yinshan; Mei, Yadong; Ren, Yufeng; Tian, Yifei; Zhang, Xiao (Frontiers in Environmental Science, 2022)
The main objective for the Three Gorges Reservoir is to help control floods and to protect the Jingjiang and Chenglingji regions in the middle reach of the Yangtze River. Hydrological measurements have demonstrated that the character of flood propagation in the Jingjiang Reach has changed significantly since the Three Gorges Reservoir became operational, meaning that flood control management must be modified accordingly. To explore the effective flood control management, a hydraulic model was developed to simulate the potential causes and impacts. For a natural flood with gradually varying discharge propagated as a diffusive wave, the celerity downside the dam fasted due to the change of the dominant property of the flood wave. For a flood event controlled by a reservoir, the wave was propagated more quickly as a surge with rapidly varying discharge. The rating curve changed for flooding processes associated with a diffusive wave versus a surge event at a particular cross-section, which changed the flow capacity in the river channel. Observed flood events in 2016 and 2017 were also simulated in the hydraulic model using different management schemes, and the modified flood propagation trends along the lower river reach were analyzed. Lastly, from these simulations, we provide suggestions on how to optimize the operation of the Three Gorges Reservoir to control flood damage and protect the Jiangjiang Reach and Chenglingji areas more effectively.